KARAKTERISTIK INDUSTRI KECIL MENENGAH PADA USAHA ROTI DI KOTA PEKANBARU - Dinko, Pandiangan; Hendro, Ekwarso; Ufira, isbah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine: (1) The origin of the factors of production of the bread industry in Pekanbaru which includes capital, raw materials, and labor. (2) How to market the results of the bread industry in the city of Pekanbaru. (3) Map of the distribution of the bread industry in the city of Pekanbaru. This study uses a quantitative descriptive method with a sample of 5 bread business units in Pekanbaru. Data collection techniques using Observation, Interview and Documentation. The results showed that: (1) The origin of capital production factors came from own capital, the bread industry's raw materials came from cooperation with distributors of raw materials that exist outside the city of Pekanbaru, the workers in the Pekanbaru industry came from inside and outside the city of Pekanbaru. (2) Marketing in all bread industries in Pekanbaru is still within the scope of Riau Province. (3) Based on the map of the distribution of Small and Medium Enterprises in the bread business in the city of Pekanbaru, this bread industry is spread in 12 districts in Pekanbaru. The sub-districts with the most industrial locations are Payung Sekaki sub-districts and Senapelan subdistricts, each of which has 7 bread industry locations.Keywords: small and medium industries, bread businesses, industrial characteristics